Pemanfaatan Akun Instagram @sejarah.banjar sebagai Sumber Sejarah Lokal Kalimantan Selatan - Fathurrahman Fathurrahman; Djono Djono (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
Technological advances open up new opportunities for documenting and disseminating local historical knowledge. Amid concerns about the fading of cultural identity, the Instagram account @sejarah.banjar is present as an innovative effort to preserve Banjar history in South Kalimantan. This research aims to examine the utilization of the Instagram account @sejarah.banjar in introducing and preserving local history in the digital era. The method used is a literature study by reviewing various scientific writings published in 2020-2024 and observing the content uploaded by the @sejarah.banjar account from 2019-2024. The results showed that the @sejarah.banjar account presents content in various formats, ranging from archival photography, illustrations, to short videos supported by trusted sources. Presentation using simple language, interesting visualizations, and contextualization of past events make history easier to understand. Account managers actively interact with followers, creating a lively discussion space. The positive impacts of this account include increased public awareness of Banjar history, the formation of a community interested in local history, and the documentation of various information about Banjar history that was previously less publicized.